2016
DOI: 10.1080/1369118x.2016.1218526
|View full text |Cite
|
Sign up to set email alerts
|

Social media and political discussion: when online presence silences offline conversation

Abstract: This paper explores the relationship between the use of social media, attitudinal strength, perceived opinion agreement with social ties, and willingness to discuss a political issue in different online and offline contexts. Unlike the anonymous environment of some Internet forums, social media are closely tied to the relationships and activities of everyday life. Social media increasingly make ties from offline contexts persistent online, and, because of the ambient nature of these technologies, awareness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(65 citation statements)
references
References 37 publications
3
56
2
4
Order By: Relevance
“…The use of social media also followed the pattern of both stimulating political talk and leading to its closure. Thus, whereas Hampton et al (2014) show evidence of a "spiral of silence" effect on social media, resulting in a generally depressive effect of social media use on offline conversation (Hampton et al, 2016), our findings demonstrate that under certain conditions people decline to silence themselves even in social media spaces populated by politically diverse contacts, which leads to the closure of (at least some) cross-cutting discourse. Troublingly, awareness of differences in that context led at least some citizens to employ social media as a sort of sorting mechanism (Hampton et al, 2016): the end result of enhanced overall conversation coupled with the cutting off of specific people should be to generate more like-minded conversational interaction, potentially adding to polarization and balkanization at the level of citizen experience.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The use of social media also followed the pattern of both stimulating political talk and leading to its closure. Thus, whereas Hampton et al (2014) show evidence of a "spiral of silence" effect on social media, resulting in a generally depressive effect of social media use on offline conversation (Hampton et al, 2016), our findings demonstrate that under certain conditions people decline to silence themselves even in social media spaces populated by politically diverse contacts, which leads to the closure of (at least some) cross-cutting discourse. Troublingly, awareness of differences in that context led at least some citizens to employ social media as a sort of sorting mechanism (Hampton et al, 2016): the end result of enhanced overall conversation coupled with the cutting off of specific people should be to generate more like-minded conversational interaction, potentially adding to polarization and balkanization at the level of citizen experience.…”
Section: Discussioncontrasting
confidence: 79%
“…In our conversational data, though Facebook did facilitate exposure to opposing views, it also carried normatively questionable outcome of conversational closure (and “unfriending”). This comports with other recent work suggesting that exposure to otherwise unknown diversity of opinion within one's digital social networks may lead some citizens to avoid offline conversation (Hampton et al, ). Thus, social media users should be more likely to cut off talk (H7).…”
Section: Wisconsin 2011–2012supporting
confidence: 88%
See 1 more Smart Citation
“…The respondents’ political interest and political preference, however, were not associated with online identity bubbles. This can be considered as surprising, as earlier research has indicated that both political interest is a significant factor in social media behavior (Boulianne, ) and social media is a beneficial interaction forum for extreme political groups especially (Hampton et al, ). Our results suggest, however, that it is political activity, not political interest or certain party affiliations, that are related to online social cliques.…”
Section: Discussionmentioning
confidence: 94%
“…H2.2 general interest in politics (Boulianne, ) and political party preference (Engesser et al, ; Hampton et al, );…”
Section: Hypothesesmentioning
confidence: 99%